THE EFFECT OF CUSTOMER TRUST AND SATISFACTION ON CUSTOMER LOYALTY AT BPR SANTI PALA IN BADUNG - Dewi, Anak Agung Istri Paramita; Amrita, Nyoman Dwika Ayu; Herlambang, Putu Gede Denny (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2025)
A banking institution is greatly influenced by customer loyalty, where loyal customers will always be loyal to the products provided by the bank, therefore, to maintain customer loyalty, the bank must build customer trust and maintain customer satisfaction by providing services or providing products needed by customers. The purpose of this study was to determine the effect of customer trust and satisfaction on customer loyalty at BPR Santi Pala in Badung. The population in the study was 2,471 customers, which were then calculated using the Slovin formula so that the number of samples became 96 respondents. The questionnaire was used as a research instrument to collect data. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, determination analysis, simultaneous significance tests (F-test), and partial significance tests (t-test). The results of the study showed that simultaneously customer trust and satisfaction influenced customer loyalty. Partially, customer trust and satisfaction had a positive and significant effect on customer loyalty